Implementation of Arabic Learning During Covid-19 Emergency in Indonesia: Hots, Mots, or Lots? - Suci Ramadhanti Febriani (Arabic Education Program IAIN Pekalongan, 2020)
The Coronavirus 2019 (COVID-19) pandemic created the challenges for Arabic learning process in Indonesian Islamic College, which is one of the important subjects for support communication in foreign languages. This study aims to describe the steps of Arabic learning at UIN Maulana Malik Ibrahim Malang and classify the implementation of Arabic learning in the HOTS, MOTS, or LOTS categories. This study uses a qualitative approach with a case study research design. The data collection include observation, interviews, and documentation. The results showed that; 1) Arabic learning at UIN Maulana Malik Ibrahim Malang adopt integration between media, methods and material based on online learning platforms or social media, 2) Arabic learning during the COVID-19 emergency include the HOTS category, this is showed when students can create conversations by integrating technology in the learning process, applying sentence structure and designing innovations in Arabic communication. The findings of this study illustrate that Arabic learning in Indonesia through technology integration can produce creativity, innovation and increase motivation in the language learning process in the COVID-19 emergency.